Advancing Media Production Research
XIII, 240 p.
Keywords: This anthology explores challenges to understanding the nature of cultural production, exploring innovative new research approaches and improvements to old approaches, such as newsroom ethnography, which will enable clearer, fuller understanding of the workings of journalism and other forms of media and cultural production.